CELEBRATION OF SCHEVCHENKO’S DAYS BY UKRAINIAN EMIGRATION AT BETWEEN-WARS CZECHO-SLOVAKIA - Karas, G. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article elucidates peculiarities of Schevchenko’s days celebrations by Ukrainian emigration at between-wars Czecho-Slovakia at the basis of archival sources. The author determines area and panorama of celebrations, their forms and peculiarities as well as their significance for development of Ukrainian musical culture abroad.